SCHOOLING AND CARE PHYSIOTHERAPY OF CHILDREN WITH MOTOR DISABILITIES (Cuestiones de Fisioterapia, 2003)
This work is an updated bibliographical revision on how the schooling of disabled boy with special educational needs is carried out, especially the motor disabled, and the physiotherapeutic support that must be given during its school stage, so that it is able to reach the different development levels and learning, which appear in the Basic Curricular Document of the School Center following the legal dispositions settled down by the Spanish central government and the autonomous of Andalusia.